Antibody Development in Patients Treated Long-Term With OnabotulinumtoxinA for Benign Essential Blepharospasm and Hemifacial Spasm. Issue 4 (December 2021) - Czyz, Craig N.; Burns, John A.; Bergstrom, Reece E.
Abstract : Background: Report the development of onabotulinumtoxinA neutralizing antibodies in patients treated consecutively for 20 years or longer for benign essential blepharospasm (BEB), hemifacial spasm (HFS), and Meige Syndrome. Methods: Prospective, randomized, cross-sectional study of 12 randomly selected patients from a single clinical practice that have been treated consecutively for 20 or more years with onabotulinumtoxinA for BEB, HFS, or Meige Syndrome. Serum samples were collected from each subject and analyzed for neutralizing antibody formation using the Mouse Protection Assay. Results: None of the tested patients (0%) displayed neutralizing antibodies to onabotulinumtoxinA. The mean duration of treatment was 27.5 years (range 22.1–34.1, SD 3.1, 95% confidence interval 25.45–29.50). Nine of the patients had a diagnosis of BEB, 2 HFS, and one Meige. Eleven of the 12 patients were women. There was no statistically significant difference in treatment dosage or interval over the course of treatment. Conclusions: The data support previous studies showing low incidence of antibody formation for botulinum A toxins with this subset of long-term treated patients. The results also provide further evidence for studies that have suggested increased onabotulinumtoxinA treatment volumes and/or decreased intervals between treatments are not due to neutralizing antibody formation and secondary non-response, but rather study designs that do not consider the titration phase of initial treatments. This study is specific to long-term treated patients, and the results cannot be generalized to patients naive to treatment.